As Colonias Portugueseas Creuista Ilustnada (Adolfo Modesto e Comp, 1889)
Keywords: 1.Conservation 保護; 2.Damage

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1889)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Carta Encyclica do Nosso Santissimo Padre Leao XIII (Typographia Universal, 1889)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Carta Encyclica do Nosso Santissimo Padre Leao XIII (Typographia Universal, 1889)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Commentarii de Casibus Reservatis, de Censuris (Ex Pyographia Marii Armanni, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Officium Parvum B. Mariae Virginis (Typis Societatis Missionum Ad Exteros, 1889)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Vida de Sao Francisco de Assis (Editor, Pe. David dos Santos Valente, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Praelectionum Philosophiae Scholasticae, Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Praelectionum philosophiae scholasticae brevis conspectus - Aa, J.-B. van der (Typis Caroli Fonteyn, 1889)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Neo-Scholasticism Handbooks; manuals; etc; Philosophy

Officium Parvum, b. Mariae Virginis - Arillo, Augusto A. (Typis Societatis Missionum Ad Exteros, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Annaes das Missoes Portuguezas - Boavida, Antonio Jose (Typographia Nacional, 1889)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Resumen de la vida del angélico joven San Juan Berchmans de la Compañía de Jesús - Cervós, Federico (Imp. y Librería de Vda. é H. de J. Subirana, 1889)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Berchmans; John; sant; 1599-1621; Condition: Fair; Hard Cover; Religion

Bibliotheca, Canonica Iusidica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Summario Da Vida Santo Ignacio De Loyola - Frei Diogo Do Rosario (Typ. Da Casa Catholica, 1889)
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.signature; Condition: Fair; Religion

Through The Heart Of Asia Over The Pamir To India - Gabriel Bonvalot (Chapman and Hall. Limited, 1889)
The French explorer, author and legislator Gabriel Bonvalot (1853-1933) received funding from the French government to lead two expeditions to Central Asia in the 1880s. This two-volume English translation by C. B. Pitman of the French original was published in 1889 and is a richly illustrated account of the second of the two Asian expeditions, in which Bonvalot and the scientist Guillaume Capus attempted to enter Afghanistan. Although the party was detained and sent back to Samarkand upon entering Afghanistan, they refused to concede defeat, as Bonvalot was determined to reach India via a trail believed to run across the Pamir and Hindu Kush mountains. In Volume 1, Bonvalot describes the journey from Marseille via Tehran to Samarkand, interspersing his narrative with observations of the climate and culture they encounter. At the Afghan border, guards warn that 'they will hack us to pieces and throw our bodies into the stream'
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Travel

Simples lectures sur les sciences, les arts et l'industrie: à l'usage des écoles primaires - Garrigues, J.; Boutet de Monvel, Louis Maurice (Librairie Hachette & Cie., 1889)
OCLC: 457336275
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Agriculture; Condition: Fair; Hard Cover; Industrial arts; Métiers; Primary School; Science; Sciences; Teaching; farming (activity or system); sciences (philosophy)

Vocabularium latino-sinicum : pronuntiatione mandarina latinis litteris - Gonçalves, Joaquim Affonso (In Collegio Sancti Josephi typis Datum, 1889)
Keywords: Chinese language; Chinese language Glossaries; vocabularies; etc; Chinois (Langue) Glossaires; vocabulaires; etc; Glossaries; vocabularies; etc; Gonçalves; Latin (Langue) Glossaires; vocabulaires; etc; Latin language; Latin language Glossaries; vocabularies; etc; Macau; USJ SEMINARY LIBRARY PROJECT; languages; 江沙維（Joaquim Afonso Gonçalves）

O Monge Pintor Poema Em Quatro Gantos - J. De Lemos (Casa Catholica Livraria, Papelaria E Typographia, 1889)
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover

O Monge Pintor Poema Em Quatro Gantos - J. De Lemos (Casa Catholica Livraria, Papelaria E Typographia, 1889)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover

exposição do dogma catholico - J. M. L. Monsabré (J. J. Reis Leitão, 1889)
Keywords: 10.Cover Damage; Fair

Manual Da Cpmposicao Litteraria: Poetica Portugueza - Jose Simoes Dias (A. Ferreira Machado, 1889)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Cursus Scripturae Sacrae, Commentarius in Ieremiam Prophetam - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Meditationes de Praecipuis Fidei Nostrae Mysteriis - Lehmkuhl, Augustini (Sumptibus Herder, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Vida Popular S. Vicente De Paulo - M. Fonseca (Jose Fructuoso Da Fonseca, 1889)
Signature
Keywords: 10.Cover Damage; 2.Damage; 22.signature; Condition: Fair; Religion

Le Bouquet da la Jeune Fille - Marchal, R. P. (Lobrairie Catholique, Perisse Freres, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Da Existengia E Do Instituto Dos Jesuitas - P. Xavier De Ravignan (Typographia De Silvestre Castanheiro, 1889)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

Oeures Choisies de Saint Francois de Sales - Pages, M. (A. Roger et F. Chernoviz, Editeurs, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Vie de Saint Francois Xabier, S. J. - R. P. D. Douhours (Desclee, de Brouwer, 1889)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Ejercicio de Perfeccion y Virtudes Cristianas - Rodriguez, Alonso (Libreria Religiosa, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Ejercicio de Perfeccion y Virtudes Cristianas - Rodriguez, Alonso (Libreria Religiosa, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Ejercicio de Perfeccion y Virtudes Cristianas - Rodriguez, Alonso (Libreria Religiosa, 1889)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Pie IX, Sa Vie, Son Histoire Son Siecle - Villefranche, J. M (Librairie et Imprimerie Vitte et Perrussel, 1889)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1889)
OCLC: 881469806
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

As Colonias Portugueseas Creuista Ilustnada (Adolfo Modesto e Comp, 1888)
Keywords: 1.Conservation 保護; 2.Damage

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1888)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Elementa artis dicendi seu Institutiones rhetoricae: ad novos scholarum usus accommodatae (Excudebat Franciscus Rosalius, 1888)
OCLC: 803629417
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Llatí Retòrica; Retòrica; Teaching

Novena da Santa Imagem de Jesus Nazareno (1888)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Sancti Bernardi, Abbatis Clarae-Vallensis, Sermones in Cantica Canticorum (Libraria Academica Wagneriana, 1888)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Summae Contra Gentiles (Ex Typographia Forzanii et Socii, 1888)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Praelectionum Philosophiae Scholasticae Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage; 6.Yellowing 變黃

Praelectionum Philosophiae Scholasticae Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage; 6.Yellowing 變黃

Praelectionum Philosophiae Scholasticae Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Praelectionum Philosophiae Scholasticae Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Praelectionum Philosophiae Scholasticae Brevis Conspectus - AA. J. Van Der (Typis Caroli Fonteyn. Bibliopolae, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Praelectionum philosophiae scholasticae brevis conspectus - Aa, J.-B. van der (Typis Caroli Fonteyn, 1888)
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Neo-Scholasticism Handbooks; manuals; etc; Philosophy

Praelectionum philosophiae scholasticae brevis conspectus - Aa, J.-B. van der (Typis Caroli Fonteyn, 1888)
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Neo-Scholasticism Handbooks; manuals; etc; Philosophy

A history of natural science and progress of discovery from the time of the greeks to the present day - Arabella B. Buckley (Edward Stanford, 1888)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

S. Francisci Xaverii, Epistolae - Arillo, Augusto A. (Typis Societatis Missionum Ad Exteros, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Heitor Servadac - Atravez do Mundo Solar (David Corazzi, 1888)
Keywords: 1.Conservation 保護; Good

Os Jesuitas - Bassano,M. Scotton (Typ. de Christovao Augusto Rodrigues, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage

Octiduum Sacrum seu S. Ignatii Exercitia - Bellecio, Aloysio (Typis Societatis Missionum Ad Exteros, 1888)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Octiduum Sacrum seu S. Ignatii Exercitia - Bellecio, Aloysio (Typis Societatis Missionum Ad Exteros, 1888)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Octiduum Sacrum seu S. Ignatii Exerictia - Bellecio, Aloysio (Typis Societatis Missionum Ad Exteros, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Oeuvres Pastorales de S. E. le Cardinal Parocchi - Bonnet, Joseph (Desclee, De Brouwer & Cie, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

L'image Miraculeuse de Notre-Dame-De- Liesse - Charpentier, L. F (L'inst- Saint- Medard, 1888)
Keywords: 1.Conservation 保護; 2.Damage

Histoire de Saint Bernard, Abbe de Clairvaux - Chevallier, M. L'abbe G (Imprimerie Saint-Augustin, 1888)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage

Histoire de Saint Bernard abbe de Claivaux - Chevallier, M. L'abbe G (Imprimerie Saint-Augustin, 1888)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage.

Los Hombres Negros Traduccion Castellana - D. Clorido Boter (Imprenta De Fidel Giro, 1888)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Bibliotheca, Canonica Iusidica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Epistolae - Francis Xavier (Typis Societatis Missionum ad Externos, 1888)
OCLC: 39014376
Keywords: 10.Cover Damage; 2.Damage; Asia; Catholic Church; Catholic Church Missions Asia; Christian saints Correspondence; Christian saints Correspondence Early works to 1800; Condition: Fair; Early works; Francis Xavier; Saint; 1506-1552; Francis Xavier; Saint; 1506-1552 Correspondence; Jesuits Asia Correspondence Early works to 1800; Jesuits Missions Asia Correspondence Early works to 1800; Missionaries Asia Correspondence Early works to 1800; Missionaries Correspondence; Missionnaires Asie Correspondance Ouvrages avant 1800; Missions; Personal correspondence; Saints chrétiens Correspondance Ouvrages avant 1800; Église catholique Missions Asie

A Paz D'alma Fructo Da Devocao A Eucharistia e do Abandono a Providencia - Francisco d'Azeredo Teixeira d'Aguilar (Livraria Internacional de Ernesto Chardon., 1888)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

Histoire Des Papes Depuis La Fin Du Moyen Age - Furcy Raynaud (Librairie Plon : Plon-Nourrit et Cie, imprimeurs-éditeurs, 1888)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; History

Commentarius in Libros Iudicum et Ruth - Hummelauer, Francisco de (Summptibus P. Lethielleux, Editoris, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Tractatus de Sacramentis in Genere - Ioannis Bapt. Franzelin (Ex Typographia Polyglotta, 1888)
Stamp
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

Anno Christao - Isla, Jose Francisco de (Antonio Dourado, Editor, 1888)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Vida de San Alonso Rodríguez coadjutor temporal de la Compañía de Jesús. - Jaime Nonell (Impr. y Librería de J. Subirana, 1888)
Condition: Binding: Hard Cover Stamps: 10 Sinageture:
Keywords: Religion; Saints Life

Les Deux Maitres De L'enfance Le Pretre et Linstituteur - L'abbe Augustin Sicard (Librairie académique Didier : Perrin et Cie, libraires-éditeurs, 1888)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Le Christ de La Tradition - Landriot, M (Librairie Victor Lecoffre, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Le Christ de La Tradition - Landriot, M (Librairie Victor Lecoffre, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Mois de Marie des Predicateurs - Marin, M. L'abbe C. (Libbrairie Religieuse et Ecclesiastique, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O Ramalhete Moral, Ao Glorioso Apostolo S. F. Xavier - Noronha, Antonio M. J. Gouveia (Poetuguese P. Press, 1888)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Vida Del P. Bernardo F. De Hoyos, De La Compania De Jesus, Arreglada Y Aumentada De Como La Escribio Y Dejo Inedita El P. Juan De Loyola - P. Jose Eugenio De Uriarte (Imprenta del Corazon De Jesus, 1888)
Stamp
Keywords: 2.Damage; Condition: Fair; Hard Cover; Religion

Antonii Ballerini E Societate Iesu, Opus Theologicum Morale - Palmieri, Dominicus (Ex Officina Libraria Giachetti, Filii et SOC., 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1888)
OCLC: 881469806
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1888)
OCLC: 881469806
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

Epistolarum - Xaverii, S. Francisci (Nas tem eapa, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Confesiones de San Agustin - Zeballos, Eugenio (Libreria Religiosa, Calle de Avino, Num. 20, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬

Confesiones de San Agustin - Zeballos, Eugenio (Libreria Religiosa, Calle de Avino, Num. 20, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Confessones de San Augustin - Zeballos, Eugenio (Capasulta, Folhas, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Confessones de San Augustin - Zeballos, Eugenio (Capasulta, Folhas, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

La vie des Saints Illustree, pour chaque jour de L'annee (Libraire de Firmin-Didot et Cie, 1887)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Obras de Santa Teresa de Jesus (Libreria Religiosa, Calle de Avino, Num. 20, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Obras de Santa Teresa de Jesus (Libreria Religiosa, Calle de Avino, Num. 20, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Obras de Santa Teresa de Jesus (Libreria Religiosa, Calle de Avino, Num. 20, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Obras de Santa Teresa De Jesus, Fundadora de la Reforma de la Orden. (Libreria Religiosa, 1887)
Keywords: Condition: Fair; Hard Cover; Religion

Obras de Santa Teresa De Jesus, Fundadora de la Reforma de la Orden. (Libreria Religiosa, 1887)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Religion

Obras de Santa Teresa De Jesus, Fundadora de la Reforma de la Orden. (Libreria Religiosa, 1887)
Keywords: Condition: Fair; Hard Cover; Religion

Obras de Santa Teresa De Jesus, Fundadora de la Reforma de la Orden. (Libreria Religiosa, 1887)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Religion

Obras de Santa Teresa de Jesus, Fundadora de la Reforma de la Orden (Libreria Religiosa, Calle de Avino, Num. 20, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Obras de Santa Teresa de Jesus, Fundadora de la Reforma de la Orden (Libreria Religiosa, Calle de Avino, Num. 20, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Pequena Hisyotia De Nossa Senhora De Lourdes (Falta o Frontespicio, 1887)
Covers missing Titlepage missing
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

S. Aur. Augustini, Hipponensis Episcopi Opuscula (apud David Nutt, 1887)
Stamp
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

TRATODOS CELEBRADOS ENTRE SUA MAGESTADE FIDELLSSIMA E A SANTA SE, E VARIOS OUTROS DOCUMENTOS RELATIVOS AO PADROADO REAL. (Impresso Na Typographia Do Seminario, 1887)
Keywords: Condition: Fair; Hard Cover

Vie de Jesus-Christ (1887)
Stamp
Keywords: 1.Conservation 保護; 14.Missing area; 6.Yellowing 變黃

Divi Aurelii Augustini Hiponensis episcopi Meditationes, Soliloquia et Manuale: accesserunt Meditationes B. Anselmi, Meditationes B. Bernardi et Idiotae viri docti Contemplationes de amore divino - Agustín; Anselmo; Bernardo; Jordanus, Raymundus (A. Jouby et Roger, 1887)
Signature
Keywords: 22.signature; Condition: Fair; Filosofía latina s.IV-V; Hard Cover; Meditaciones; Religion; Teología latina s.IV-V

Compendio da Historia da Portugal Para Uso Dos Alumnos - Antonio Lopes Pereira (Typographia do Seminario, 1887)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

Geographia Geral actualisada - Botelho, José Nicolau Raposo (Livraria Internacional de Ernesto Chardon., 1887)
OCLC: 432757146
Keywords: 2.Damage; Condition: Fair; Hard Cover

Ollendorff e Benot: Novo Methodo para Aprender A Lingua Latina: adequado para uso dos portugueses e brazileiros - Branco, Manuel Bernardes (Tavares Cardoso, 1887)
OCLC: 958970631

Cursus Scripturae Sacrae, Historica et Critica Introductio - Cornely, Rudolphus (Sumptibus P. Lethielleux, Editoris, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Biblia Sacra Juxta, Vulgatae - Fillion, Aloisius Claudius (Librairie Letouzey et Ane, 1887)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Tractatus de SS. Eucharistiae - Franzelin, Ioannis Bapt. (Ex Typographia Polyglotta, 1887)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Traite elementaire de physique - Ganot, A. (Librairie Hachette Et C, 1887)
OCLC: 1344459678
Keywords: 10.Cover Damage; 16.Waterstains; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Science Study and teaching

Vie Des Saints - Guerin, Paul (Societe Generale de Librairie Catholique, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Compendium Theologiae Moralis - Gury, P. Ioannis Petri (Ex Typographia Polyglotta, 1887)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Geographia Geral Actualisada e Posta em Harmonia Com o Novo Programma Para o Ensino nos Lyceus Coordenada - Jose Nicolau Raposo Botelho (Livraria Internacional de Ernesto Chardron, 1887)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Execicios de Perfeicao e Virtudes Christas - Jose Pinto De Moura (Antonio Dourado, 1887)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

Commentarius in Isaiam Prophetam - Knabenbauer, Iosepho (Summptibus P. Lethielleux, Editoris, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Commentarius in Isaiam Prophetam - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Les Gloires de Marie - Liguori, Alphonse de (Desclee, De Brouwer & Cie, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Les Gloires de Marie - Liguori, Alphonse de (Desclee, De Brouwer & Cie, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Les Gloires de Marie - Liguori, Alphonse de (Desclee, De Brouwer & Cie, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Jeanne D'arc - Marius Sepet (Alfred Mame et Fils, 1887)
Keywords: Condition: Fair; Hard Cover

Documentos apresentados ás cortes na sessão legislativa de 1887 pelo Ministro e Secretario d'Estado dos Negocios Estrangeiros - Ministério dos Negócios Estrangeiros, Portugal (Imprensa Naciona, 1887)
Signature
Keywords: 10.Cover Damage; 2.Damage; 22.signature; Condition: Fair; Hard Cover

Selecta e veteribus scriptoribus loca, iussu regis fidelissimi in lucem edita et scholarum linguae latinae usvi adcommodata - Moura, Vicente Gomes de (Ex typ. Academico Regia, 1887)
OCLC: 954131007
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Latin language; languages

Mitras Lusitanas - Nazareth, Casimiro C. (Imp. Nacional, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Institutiones Philosophiae Scholasticae - P. Josepho Mendive (Ex typographia viduae de cuesta et Fil, 1887)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Philosophy

Exericcios de Perfeicao e virtudes Christas - Pe. Affonso Rodrigues (Antonio Dourado, 1887)
Title Page Missing
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Missing Area; Religion

Exericcios de Perfeicao e virtudes Christas - Pe. Affonso Rodrigues (Antonio Dourado, 1887)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

La Vierge Mere, D'apres la Theologie - Petitalot, R. P. (Retaux-Bray, Libraire-Editeur, 1887)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Exercitia Spiritualia S. P. Ignatii De Loyola - R. P. Joanne Roothaan (Typis et Sumptibus Instituti Literarii, 1887)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

O Liberalismo e Peccado - Salvani, D. Felix Sarda (Editor, J. J. Reis Leitao, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

A Carta Do Santo Padre Leao XIII ao - Samodaes, Donde de (Typographia da Palavra, 1887)
Keywords: 1.Conservation 保護; Good

Uma Visita a Lourdes - Samodaes, Donde de (Jose Fructuoso Da Fonseca, 1887)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cancioneiro de Leao XIII, Sua Santidade - Sancto, Pe. Joaquim (Manuel Malheiro, 1887)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Pictorial Lives of the Saints with reflections for every day in the year - Shea, John Gilmary (Benziger Brothers, 1887)
Stamp
Keywords: 1.Conservation 保護; 2.Damage

A Bulla da Santa Cruzada (Libraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Boletim da Provincia de Macau e Timor (Typographia Mercanitil, 1886)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Novena Dicta da Graca em Honra de S. Francisco Xavier (Typographia da Cruz do Operario, 1886)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeuvres de Monseigneur L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Oeuvres de Monseigneur, L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Oeuvres de Monseigneur, L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Sermons of the Rev. Joseph Farrell (M. H. Gill and Son LTD., 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

A Religiao em Face da Sciencia - Arduin, Abbade Alexis (Libraria Academica, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Catecismo de la doctrina Cristiana - Astete, P. Gaspar (Editorial Saturnino Calleja, S. A, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Bohemia do espirito, por Camillo Castello Branco - Castelo Branco, Camilo (Livraria Civilisação, 1886)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover

Les Commentaires Sur La Guerre des Gaules - Cesar (Hachette et Cie, 1886)

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Cursus Scripturae Sacrae, Historica et Critica Introductio - Cornely, Rudolphus (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Coleccion de Platicas dominicales - D. Antonio Maria Claret Y Clara (Liberia Religiosa, 1886)
Stamp of St. Joseph Seminary
Keywords: Good

Platicas Morales para Todos los Domingos Del Ano - D. Ramon Lastiesas (Libreria Religiosa, 1886)
stamp of seminario de S. Jose
Keywords: Good

Bibliotheca, Canonica Iuridica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Bibliotheca, Canonica Iuridica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Curso de Misiones Apostolicas, Platicas Instructivas - Gual, Pedro (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Commentarius in Libros Samuelis seu I et II Regum - Hummelauer, Francisco de (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Caminho da Perfeicao - Jesus, Theresa de (Typographia Elzeviriana, 1886)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Commentarius in Librum Iob - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Commentarius in Prophetas Minores - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Cursus Scripturae Sacrae, Commentarius in Rophetas Minores - Knabenbauer, Iosepho (Summptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Platicas Morales para Todos Los Domingos del Ano - Lastiesas, D. Ramon (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Thesouro do Sacerdote - Mach, Jose (Livraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Thesouro do Sacerdote - Mach, Jose (Livraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Congregacoes da Immaculada Viregem Maria E de S. Luiz Gonzaga - P. Antonio Maria Alves (Seminario De S. Jose, 1886)
Decorridos apenas poucos mees depois da minha chegada a Zi-ka-wei, em 1895.senti-me docemente impellido a proseguir na ideia, que antes tivera, de indagar os principios das Congregações de N. Senhora no imperio florido, e ligar depois os tempos antigos aos modernos, mostrando os sazonados fructos de bencão, que ellas produziram sempre, nestas remotas paragens. A empreza que, em Macau, se me afigurara impossivel por escassez de documentos, pareceu-me então de facil alcance, vendo-me em meio de uma grande bibliothca, fornecida de livros selectos. Dei-me, pois, ao trabalho de folhear alguns, e em breve, junctei uns dadosinhos preciosos, que começo hoje, meus amados Congregados, a apresentar-vos, em toda a sua simmplicidade. Possam elles despertar, em vossos coraçõesjuvenis, novos brios e alentos no amor para com a Mãe celeste, pela practica das Regras da Congregaçao a qual tendes a dita de pertencer
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Travel

Historia Sagrada do Antigo e novo Testamento - Roquete, J. I (Guillard, Aillaud, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Manuel technique d'anatomie végétale; guide pour l'étude de la botanique microscopique - Strasburger, Eduard (F. Savy, 1886)
OCLC: 18129004
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Microscope and microscopy Technique; Microscopie Technique; Microscopy Technique; Plant anatomy; Plantes Anatomie

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1886)
OCLC: 881469806
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1886)
OCLC: 881469806
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1885)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Casus Conscientiae, his praesertim temporibus accommodati (Typis Alfredi Vromant, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Casus Conscientiae, his praesertim temporibus accommodati (Typis Alfredi Vromant, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Letters de M. Olier (Librairie Victor Lecoffre, 1885)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Um Bispo Segundo Deus ou Memorias Para a vida de D. Manuel De Aguiar (Typ de Reis Leitao, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

As Chammas Do Amor De Jesus - Abbade D. Pinnard (Typ. da Palavra, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Religion

As Chammas Do Amor De Jesus - Abbade D. Pinnard (Typ. da Palavra, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Vidas de Los Hermanos - Alvarez, Paulin (1885)
Keywords: 1.Conservation 保護; 2.Damage

A religião em face da sciencia: lições sobre o accordo entre os dados da revelação biblica e as theorias scientificas modernas - Arduin, Alexis; Almeida Netto, Antonio Maria d'; Almeida, Jose Maria d' (Livraria Académica, Editora de José Maria d'Almeida, 1885)
OCLC: 1286748899
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion; Religión y ciencia

A religião em face da sciencia: lições sobre o accordo entre os dados da revelação biblica e as theorias scientificas modernas - Arduin, Alexis; Almeida Netto, Antonio Maria d'; Almeida, Jose Maria d' (Livraria Académica, Editora de José Maria d'Almeida, 1885)
OCLC: 1286748899
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion; Religión y ciencia

Meditacoes Sacerdotaes - Chaignon, R. P. (Typ. de A. J. da Silva Teixeira, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Meditacoes Sacerdotaes - Chaignon, R. P. (Typ. de A. J. da Silva Teixeira, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Scripturae Sacrae, Historica et Critica Introductio - Cornely, Rudolphus (Sumptibus P. Lethielleux, Editoris, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Everyday life in China or Scenes along river and road - Dukes, Edwin Joshua (The Religious Tract Society, 1885)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Bibliotheca - F. Lucii Ferraris (Ex Typographia Polyglotta, 1885)
Stamp of St. Joseph Seminary
Keywords: Good

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Les Peres Apostoliques et Leur Epoque - Freppel, Mgr (Bray et Retaux, Libraires-Editeurs, 1885)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Hygiene social applicada á nação portugueza: conferencias feitas no Porto. 1. sér - Jorge, Ricardo (Imprensa Civilizacao, 1885)
OCLC: 956535174
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Portugal; Public Health; Public health; Santé publique; public health

Nouveau Commentaire Litteral, Critique et Theologique, avec rapport aux testes primitifs, sur tous les lives des divines ecritures. - M. Le Docteur J. F. D'Allioli (Chez Louis Vives, 1885)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm (Only Cover); 2.Damage

O escholiaste portuguez ou, Subsidios litterarios, grammaticaes, philologicos e rhetoricos compilados dos melhores auctores e divididos em tres partes accommodadas ao estudo elementar e complementar da lingua portugueza - Netto, Antonio Maria d'Almeida (Livraria Ferreira, 1885)
OCLC: 550608752
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Portugais (Langue); Portuguese language; Portuguese language Grammar; Portuguese language Grammar 1870-; Since 1870; languages

Lettres de M. Olier - Oliver, M. (Librairie Victor Lecoffre, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Elements De Botanique - P. Duchartre (Librairie J.- B. Bailliere et Fils, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Teaching

Les Petits Bollandistes- Vies Des Saints - Paul Guerin (Bloud et Barral, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; Religion

O Culto Catholico Com Solemnidade e Sem Ministros Sagrados - Pimentel, D. Joao (Typ. Virgem Immaculada, 1885)
Keywords: 1.Conservation 保護; 2.Damage

Sanctorum Patrum Opouscula Selecta de S. Marino - Severi Sulpicii (Typis Wagnerianis, 1885)
Keywords: 1.Conservation 保護; 2.Damage

古史参 箴卷三 - 沈, 則寬; 南, 志恆; 應, 儒望 (慈母堂, 1885)
OCLC: 695516079
Keywords: Catholic Church–China

As Colonias Portugueseas Creuista Ilustnada (Adolfo Modesto e Comp, 1884)
Keywords: 1.Conservation 保護; 2.Damage

Biblia Popular Illustrada Pelo, Abbade Drioux (Typ. de Arthur Jose de Souza & Irmao, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Biblia Popular Illustrada Pelo, Abbade Drioux (Typ. de Arthur Jose de Souza & Irmao, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1884)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Dictionnaire, Latin- Francais, Redige sur un Noveau Plan (Librairie Hachette Et C, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Hard Cover

Novo Mensageiro do Coracao de Jesus (Typographia da Cruz do Operario, 1884)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

S. Aurelii Augustini Hipponensis Episcopi in Joan nis Evangelium (apud Lethielleux, 1884)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Vie de Mer Dupanloup Eveque D'Orlevans (Librairie Poussielegue Freres, 1884)
Keywords: 1.Conservation 保護; 18.Bookworm

Traite De Manipultions De Chimie - A. Riviere; CH. Riviere (Libraire des Corps des Ponts et Chausses et des Mines, 1884)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Science Study and teaching

El hombre feliz: independiente del mundo y de la fortuna : ó arte de vivir contento en qualesquier trabajos de la vida : obra escrita en portugues - Almeida, Theodoro de (Libreri Religiosa, Calle De Avino, 1884)
OCLC: 24086836
Keywords: Bonheur; Condition: Fair; Contentement; Contentment; Hand writing; Happiness; Hard Cover

A religião em face da sciencia : lições sobre o accordo entre os dados da revelação biblica e as theorias scientificas modernas - Antonio Maria d' Almeida Netto (Typographia Universal, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Cerimonial Romano - Antunes, Manuel Damaso (typographia do Diario da Manhá, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

A Religiao em Face da Sciencia Cosmogonia - Arduin, Abbade Alexis (1884)
Keywords: 1.Conservation 保護; 2.Damage

Meditacoes Sacerdotaes - B.R. Chaignon (Ernesto Chardron, 1884)
Keywords: Fair

Dictionnaire universel des sciences, des lettres et des arts ... avec l'explication et l'etymologie de tous les termes techniques, l'histoire sommaire des diverses branches des connaissances humaines, et l'indication des principaux ouvrages qui s'y rapportent .. - Bouillet, Marie Nicolas (Hachette, 1884)
OCLC: 14088251
Keywords: Condition: Fair; Dictionaries; Encyclopedias and dictionaries; French; Encyclopédies et dictionnaires français; Hard Cover

Cours de Mathematiques - Charles de Comberousse (Gauthier- Villars, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Teaching

O direito ao alcance de todos, ou O advogado de si mesmo. Diccionario de direito usual, contendo as noções praticas do direito e modelos e formulas d'alguns actos sobre materia civil, commercial, administrativa, criminal, ecclesiastica e do processo - Francisco Antonio Veiga (Livraria de Antonio Maria Pereira, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Law

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Both covers Missing
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Both covers Missing
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; Philosophy; Religion

O Padre Ao Altar - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

O Padre Ao Altar - Francisco Luís de Seabra (Ernesto Chardron, 1884)
Stamp
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

No Presbyterio e No Templo - Freitas, Padre Senna (Fornecedores da Casa de Bragnca, 1884)
Keywords: 1.Conservation 保護; 2.Damage

La Terre Sainte, - Guerin, Victor (1884)
Keywords: 10.Cover Damage; 18; 2.Damage

Sanctorum patrum opuscula selecta ad usum praesertim studiosorum theologiae. Series altera - H. Hurter (Lethieleux, 1884)
OCLC: 731190641
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Fathers of the church; Pères de l'Église; Religion

Sanctorum patrum opuscula selecta ad usum praesertim studiosorum theologiae. Series altera - H. Hurter (Lethieleux, 1884)
OCLC: 731190641
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Fathers of the church; Pères de l'Église; Religion

Recordacoes e Impressores de Viagem - Joao Baptista De Freitas Leal (Typ. do Diario de Noticias, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Travel

Vie de Mgr Dupanloup - Lagrange, M. L'abbe F. (Librairie Poussielegue Freres, 1884)
Keywords: 1.Conservation 保護; 15.Stain 污漬.; 18.Bookworm; 2.Damage

Panorama Des Predicateurs Ou Repertoire Pour L'improvisation et La Composition Du Sermon - M. l'Abbe C. Martin (Librairie Religieuse Et Ecclesiastique De Martin neveu et Audier, 1884)
Keywords: 16.Waterstains; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Novo Diccionario Portuguez- Latino - Manoel Bernardes Branco (Livraria Ferreira, 1884)
Covers Missing
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Dictionaries; Missing Area; languages

Le Chretien Eclaire sur La Nature et L'usage Des Indulgences - Maurel, P. A. (J. B. Pelagaud, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Compendio De Historia Universal - Mons. Daniel (Livraria Portuense de Clavel, 1884)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

Pensamentos ou Reflexoes Christas - Nepveu, R. P. F (Imprensa Commerical, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Pensamentos ou Feflexoes Christas - Nepvieu, R. P. F. (Doutor Jose Rodrigues Cosgaya, 1884)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O escholiaste portuguez ou, Subsidios litterarios, grammaticaes, philologicos e rhetoricos compilados dos melhores auctores e divididos em tres partes accommodadas ao estudo elementar e complementar da lingua portugueza - Netto, Antonio Maria d'Almeida (Livraria Ferreira, 1884)
OCLC: 550608752
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Portugais (Langue); Portuguese language; Portuguese language Grammar; Portuguese language Grammar 1870-; Since 1870; languages

Nova grammatica portugueza: compilada de nossos melhores auctores e coordenada para uso das escholas - Oliveira, Bento Josʹe de (Livraria de J.A. Orcel, 1884)
OCLC: 24270360
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Portugais (Langue) Grammaire; Portugues (gramatica); Portuguese language Grammar; languages

cerimonial romano - R. P. le Vavasseur (typographia do Diario da Manhá, 1884)
hand-writting, sign, stamp of seminario de s. jose macau
Keywords: Good

Historia Verdadeira da Inquisicao - Rodrigo, D. Francisco Xavier G. (Centro de Propaganda CAtholica Em Portugal, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1884)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; Religion

R. P. Jacobi Tirini S. J. in Universam S. Scripturam - Zachariae P.; Brunengo P. Josephi (Ex Typ. Pontif. et Archiepiscopali, 1884)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius. - Zachariae P.; Brunengo P. Josephi (Ex. Typ. Pontif. et Archiepiscopali, 1884)
Stamp
Keywords: Fair

Boletim da Provincia de Macau e Timor (Typographia Mercanitil, 1883)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

La Persecution Beligieuse en Angleterre (Societe de Saint Augustin, Desclee, de Brouwer et Cie, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

salmanticensis cursus theologicus (E. societate generali librariae catholicae, 1883)
stamp of seminário de s. jose biblioteca, stamp of missions etrangeres no. 1, Battery Path Hong Kong
Keywords: 18.Bookworm (Only Cover); Good

salmanticensis cursus theologicus (E. societate generali librariae catholicae, 1883)
stamp of seminário de s. jose biblioteca, stamp of missions etrangeres no. 1, Battery Path Hong Kong
Keywords: 18.Bookworm (Only Cover); Good

Bento Jose Labre, Ultimo Santo Inscripto no Agiologio - Aguilar, Francisco de Azeredo Teixeira (Editor, Jose Fructuoso da Fonseca, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

La Persecution Religieuse en Angleterre - Bestombes, L'abbe (1883)
Keywords: 1.Conservation 保護; 2.Damage

La Persecution Religieuse en Angleterre - Bestombes, L'abbe (1883)
Keywords: 1.Conservation 保護; 2.Damage

Trabalhos Postoraes - Boavida, Antonio Jose (typographia do Diario da Manhá, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Logares selectos dos classicos Portuguezes: nos principaes generos de discurso em prosa, para uso das escholas - Borges de Figueiredo, Antonio Cardoso (Livraria Central de J. Diogo Pires, 1883)
OCLC: 63813571
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Teaching

Historire de Sainte Monique - Bougaud, M. L'Abbe (1883)
Keywords: 1.Conservation 保護; 2.Damage

Meditacoes: Para Todos os Dias do Anno - Francisco Luís de Seabra (Ernesto Chardron, 1883)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy

Meditacoes: Para Todos os Dias do Anno - Francisco Luís de Seabra (Ernesto Chardron, 1883)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy

R. P. Jacobi Tirini S. J. in Universam S. Scritpturam - Grunengo, P. Jospehi (Ex Typ. Pontif. et Archiepiscopali, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

R. P. Jacobi Tirini S. J. in Universam S. Scritpturam - Grunengo, P. Jospehi (Ex Typ. Pontif. et Archiepiscopali, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Meditacoes para Todos os Dias do Anno - Hamon, M. (Ernesto Chardron, Editor, 1883)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Os Episodios Miraculosos de Lourdes - Lasserre, Henrique (Typographia da Palavra, 1883)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Saint Bruno et L'ordre des Chartreux - Lefebvre, L'abbe (Librairie Catholique Internationale, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Saint Bruno et L'ordre des Chartreux - Lefebvre, L'abbe (Librairie Catholique Internationale, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Abridgment of the History of England with cont. from 1688 to the 45. year of the reign of Queen Victoria - Lingard, John; Burke, James (Duffy [u.a.], 1883)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; History

Les Splendeurs De La Foi - M. l'abbe Moigno (Bleriot et Gautier, 1883)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1883)
Keywords: Condition: Fair; Hard Cover; Religion

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1883)
Signature
Keywords: 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; Religion

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1883)
Signature
Keywords: 2.Damage; 22.signature; Condition: Fair; Hard Cover; Religion

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1883)
OCLC: 881469806
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius. - Zachariae P.; Brunengo P. Josephi (Ex. Typ. Pontif. et Archiepiscopali, 1883)
Stamp
Keywords: Fair

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius. - Zachariae P.; Brunengo P. Josephi (Ex. Typ. Pontif. et Archiepiscopali, 1883)
Stamp
Keywords: Fair

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius. - Zachariae P.; Brunengo P. Josephi (Ex. Typ. Pontif. et Archiepiscopali, 1883)
Stamp
Keywords: 18.Bookworm; Fair

Athanasii, archiepiscopi Alexandrini (apud Bloud & Barral, 1882)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1882)
Keywords: 18.Bookworm; 2.Damage

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1882)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Novo Mensageiro do Coracao de Jesus (Typographia da Cruz do Operario, 1882)
Keywords: 1.Conservation 保護; 2.Damage

R. P. Jacobi Tirini S. J. in Universam S. Scripturam - Brunengo, P. Josephi (Ex Typ. Pontif. et Archiepiscopali, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius - Brunengo P. Josephi (Ex Typ. Pontif. et Archiepiscopali, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

meditações para todos os dias do anno - Hamon, M. (1882)
title page and Page 1-4 are missing
Keywords: 13.Page missing; 18.Bookworm; Condition: Poor; Hard Cover

meditações para todos os dias do anno - Hamon, M. (1882)
title page and Page 1-4 are missing
Keywords: 13.Page missing; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Meditacoes Para Todos os Dias do Anno - Hamon, M. (Ernest Chardron, Editor, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

exposition du Dogme Catholique - J. M. L. Monsabré (P. Lethielleux, 1882)
stamp of Bibliethéque de Nazareth
Keywords: Good

Vie de Saint Dominique - Lacordaire, R. P. Henri-Dominique (Libraire Poussielgue Preres, 1882)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Historia Verdadeira da Inquisicao - Rodrigo, D. Francisco Xavier G. (Centro de Propaganda CAtholica Em Portugal, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Confesiones del Beato Alonso de Orozco - Rojsa, Hernando de (Imprenta de Amigos del Pais, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

As Formulas dos Contractos ou Guia Portatil do Tabelliado - S. R. de Darualho (Typ. de Andre J. Pereira & Filho, 1882)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 22.signature; Condition: Poor; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 2.Damage; 22.signature; 28.Iron-gall ink; Condition: Poor; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 22.signature; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 22.signature; Condition: Fair; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Poor; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; History

historiarum libri, qui supersunt, cum deperditorum fragmentis et epitomis omnium, - t. livii patavini (EX TYPOGRAPHIA academico-regia, 1882)
Keywords: 18.Bookworm; 2.Damage; 22.signature; Condition: Poor; Hard Cover; History

Les Auteurs grecs expliqués d'après une méthode nouvelle, par deux traductions françaises, l'une littérale et juxtalinéaire ... l'autre correcte et précédée du texte grec, avec des arguments et des notes ... Thucydide. Morceaux choisis - Thucydide (Hachette, 1882)
OCLC: 458299381
Keywords: Condition: Fair; Hard Cover; languages

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1882)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Religion

Universam S. Scripturam commentarius - Tirinus, Jacobus (Petri Marietti, 1882)
Signature
Keywords: 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; Religion

Vie Populaire de Saint Benoit-Joseph Labre par Un Prêtre Mariste - Un Prêtre Mariste (imprimeries-Librairies de l'ceuvre de Saint-Paul, 1882)
Keywords: 2.Damage; Condition: Fair; Paperback; Religion

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1882)
OCLC: 881469806
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry; Latin; Poésie élogieuse latine; languages

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius - Zachariae P.; Brunengo P. Josephi (Ex Typ. Pontif. et Archiepiscopali, 1882)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

R. P. Jacobi Tirini S. J. in Universam S. Scripturam Commentarius. - Zachariae P.; Brunengo P. Josephi (Ex. Typ. Pontif. et Archiepiscopali, 1882)
Stamp
Keywords: Fair

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1881)
Keywords: 18.Bookworm; 2.Damage

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1881)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1881)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Diccionario Contemprotaneo da Lingua Portugueza (Imprensa Nacional, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Mez de S. Francisco D'assis, (1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 14.missing area; 6.Yellowing 變黃

Saint Martin - a. lecoy de la marche (Alfred Mame, 1881)
Keywords: 2.Damage; Hard Cover; Religion

Vie Populaire de Saint Benoit-Joseph Labre - A. M. D. G (Imprimerie de l'oeuvre de Saint-Paul, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

La Doctrine sur La Vierge Marie ou Marialogie de Saint Thomas d Aquin - Bourquard, Laurent-Casimir (Louis vives, Libraire-Editeur, 1881)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

La Devocion al Sagrado Corazon de Jesus - Croiset, R. P. Juan (Libreria Religiosa, Calle de Avino, Num. 20, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Histoire de Saint Francois de Xavier - Daurignac, J. M. S. (Bray et Retaux, Libraires-Editeurs, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Histoire de Saint Francois de Xavier - Daurignac, J. M. S. (Bray et Retaux, Libraires-Editeurs, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage

Obras - Uma Noticia Biographica Vasconcellos D. - de Ornellas, Ayres (Ernesto Chardron, 1881)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Saint Paul Etudie em Vue La Predication - Doublet, M L'Abbe (Berche et Tralin, Editeurs, 1881)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Saint Paul Etudie en Vue de La Predication - Doublet, M L'Abbe (Berche et Tralin, Editeurs, 1881)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Saint Paul etudie en vue de La Prediction - Doublet, M L'Abbe (Berche et Tralin, Editeurs, 1881)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

A Biblia Sagrada - Figueiredo, Antonio Pereira de (Na Officina de Simao, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Les Auteurs grecs : expliqués d'après une méthode nouvelle : par deux traductions françaises, l'une littérale et juxtalinéaire présentant le mot a mot français en regard des mots grecs correspondants l'autre correcte et précédée du texte grec : avec des sommaires et des notes - jean chrysostome (Librairie Hachette Et C, 1881)
Keywords: Condition: Fair; Hard Cover; languages

Iliade Chant II - Julien, M. L'abbe (Libraire Poussielgue Freres, 1881)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Fabiola ou L'eglise des Catacombes - Pascal- Marie, F. (Vve, H. Casterman, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

La Devocion al Sagrdo Corazon de Jesus - Penalosa, P. Pedro de (Libreria Religiosa, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Chemin de Croix des Enfants de Marie - Redon, Chanoine Elie (Aubanel Freres, Editeurs, 1881)
Signature
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Oriente Conquistado a Jesus Schristo Pelos Padres da Compandhia de Jesus - Souza, Francisco de (Na Typographia Examiner, 1881)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1880)
Keywords: 18.Bookworm; 2.Damage

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1880)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Manuale Sacrarum Caeremoniarum in Libros Octos Digestum (Ex Typographia Ludovici Cecchini, 1880)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Quinti Septimii Florentii Tertulliani (apud Bloud & Barral, 1880)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃.

Sancti Patris Nostri Joannis Damasceni (apud Bloud & Barral, 1880)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Theologia Dogmatica Polemica, Scholastica et Moralis (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Historiae Seu Vitae Sanctorum - D.D. Laurentio Gastaldi (EX TYPOGRAPHIA PONTIFICIA, 1880)
Keywords: Fair

Theoria das provas - Franeiseo Augusto das neves e castro (Ernesto Chardron, 1880)
hand writting
Keywords: 2.Damage; Hard Cover

Ensaios do Pulpito - G. A. De (Livraria Internacional de Ernesto Chardon., 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

De la Oracion y Consideracion - Granada, Luis de (Libreria Religiosa, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

De la Oracion y Consideracion - Granada, Luis de (Libreria Religiosa, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Theologia Dogmatica, Polemica, Scholastica et Moralis - Killber, Henrico (Berche et Tralin, Editeurs, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Saint Vincent de Paul et Sa Mission Sociale - Loth (Librairie de d. Dumoulin et Cie, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Panorama des Predicateurs - M. L. 'Abbe C. Martin (Martin Neveu et Audier, 1880)
Keywords: 2.Damage

Panorama Des Predicateurs Ou Repertoire Pour L'improvisation et La Composition Du Sermon - M. l'Abbe C. Martin (Librairie Religieuse Et Ecclesiastique De Martin neveu et Audier, 1880)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

dictionnaire universel des sciences, desletters et des arts Pour les sciences, pour les lettres, pour les arts - M.-N. Bouillet (Librairie Hachette Et C, 1880)
Keywords: 12. Fragment; 18.Bookworm; 2.Damage; Dictionaries; Hard Cover

Du Droit et Du Devoit - Meric, L'abbe Elie (Societe Generale de Librairie Catholique, 1880)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Manual dos Confessores - Padre J. Gaume (EM Casa De A . R. Cruz Coutinho., 1880)
with hand writing note
Keywords: 10.Cover Damage; 22.signature; 22.stamp; Condition: Fair; Paperback; Religion

Manual dos Confessores - Padre J. Gaume (Em Casa de A. R. da Cruz Coutinho, 1880)
sign
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); Fair

Catalogo Biografico de los Religiosos Franciscanos - Platero, Eusebio Gomez (Imprenta de Real Colegio de Santo Tomas, 1880)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage